2002
DOI: 10.1074/jbc.m209165200
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent Protein Kinase and Ca2+Influx through L-type Voltage-gated Calcium Channels Mediate Raf-independent Activation of Extracellular Regulated Kinase in Response to Glucagon-like Peptide-1 in Pancreatic β-Cells

Abstract: Glucagon like peptide-1 (GLP1) is a G s -coupled receptor agonist that exerts multiple effects on pancreatic ␤-cells, including the stimulation of insulin gene expression and secretion. In this report, we show that treatment of the mouse pancreatic ␤-cell line MIN6 with GLP1 leads to the glucose-dependent activation of Erk. These effects are mimicked by forskolin, a direct activator of adenylate cyclase, and blocked by H89, an inhibitor of cAMP-dependent protein kinase. Additionally, we provide evidence that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 43 publications
5
123
2
1
Order By: Relevance
“…Alternatively, calcium may act locally near the membrane and close to the mouth of the L-type voltage-dependent calcium channel. A model has been proposed in which calcium binds calmodulin tethered to the channel, causing it to associate with the IQ motif of the channel; this association then leads to the activation of the Ras-mitogen-activated extracellular signal-regulated kinase kinase-ERK1/2 MAPK signalling pathway and sustained CREB Ser119 phosphorylation [30,31]. In addition to these kinases, the calcium/ calmodulin-dependent protein phosphatase calcineurin is also required for CREB activation by membrane depolarisation [3,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, calcium may act locally near the membrane and close to the mouth of the L-type voltage-dependent calcium channel. A model has been proposed in which calcium binds calmodulin tethered to the channel, causing it to associate with the IQ motif of the channel; this association then leads to the activation of the Ras-mitogen-activated extracellular signal-regulated kinase kinase-ERK1/2 MAPK signalling pathway and sustained CREB Ser119 phosphorylation [30,31]. In addition to these kinases, the calcium/ calmodulin-dependent protein phosphatase calcineurin is also required for CREB activation by membrane depolarisation [3,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK1/2 occurs via phosphorylation and translocation to the nucleus and ERK1/2 already present in the nucleus is phosphorylated upon stimulation. Glucose stimulation has been demonstrated to activate both isomers of ERK in β cells Gomez et al, 2002;Khoo and Cobb, 1997). Phosphorylation of ERK1/2 in response to GLP-1 treatment has been demonstrated in several insulinoma cell lines Gomez et al, 2002) and more recently by GLP-1 (Trumper et al, 2005) and Ex-4 in human islets.…”
Section: Mapk and Pi3 Kinase Related Pathwaysmentioning
confidence: 99%
“…Glucose stimulation has been demonstrated to activate both isomers of ERK in β cells Gomez et al, 2002;Khoo and Cobb, 1997). Phosphorylation of ERK1/2 in response to GLP-1 treatment has been demonstrated in several insulinoma cell lines Gomez et al, 2002) and more recently by GLP-1 (Trumper et al, 2005) and Ex-4 in human islets. The earlier studies in the insulinoma cell lines reported conflicting data indicating either a Raf/Ras-independent mechanism or inconsistent Raf activation due most probably to the different cell types used in the experiments.…”
Section: Mapk and Pi3 Kinase Related Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose and GLP-1 have been shown to activate ERK in numerous beta cell lines and in murine islets [3][4][5]. How-ever, the published results are inconsistent with respect to whether this activation is dependent on [3] or independent of [4,5] Ras and Raf kinases.…”
Section: Introductionmentioning
confidence: 99%